A Study of the Optical Properties of CuBr Thin Film - AI-Dahan, Z.T.; Abdulrida, M.C.; AI-Ani, Z.T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we have studied the optical properties of CuBr thinfilms.  Different  sample  thicknesses  have  been  prepared  by  using thermal evaporation  technique with 14.4 runlsec as the average deposition rate and 1 00Â°C as the substrate temperature.